Clinical Pearls in Pediatric Otolaryngology: A Video Forum. (23rd August 2013) - Parikh, Sanjay R.; Roy, Soham; Derkay, Craig S.; Hartnick, Christopher J.; White, David R.; Kazahaya, Ken; Rutter, Michael J.; Goudy, Steven L.; Zdanski, Carlton
Abstract : Program Description: This video‐based forum will provide audience members with state of the art concepts in pediatric otolaryngology. The speakers consist of: Carlton Zdanski: Transoral Robotic Surgery in Children: Indications and Results; Christopher Hartnick: Bevacizumab (Avastin) injection for pediatric RRP; Craig Derkay: Modifications of the Seldinger technique to secure the difficult pediatric airway; David White: Endoscopic division of the sternocleidomastoid muscle for treatment of torticollis; Ken Kazahaya: Endoscopic assisted otologic surgery; Michael Rutter: Tracheotomy tube fenestration; Sanjay Parikh: Diagnosis of sleep induced laryngomalacia; Soham Roy: Radiofrequency ablation of pediatric oral cavity lesions; Steven Goudy: Video‐assisted pharyngeal surgery. Educational Objectives: 1) Consider contemporary airway management ideas for tracheotomy tubes, recurrent papillomatosis, and laryngomalacia. 2) Describe novel endoscopic laryngopharyngeal techniques with robotics, radiofrequency, and video‐assistance. 3) Implement novel endoscopic otologic and neck techniques.